2022
DOI: 10.3390/antibiotics11091229
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Study on Antimicrobial Usage and Resistance in the Dairy Chain: A Situation Analysis and Solutions by Stakeholders from Punjab, India

Abstract: The rising prevalence of antimicrobial resistance in animal foods and injudicious antibiotic use in the dairy sector pose significant threats to public health. Focus group discussions (FGDs) and key informant interviews (KIIs) were conducted with a strategic sample of four stakeholder groups (114 participants) associated with antibiotic usage in the dairy sector of Punjab. The FGDs were conducted among veterinarians (n = 56), para-veterinarians (n = 28), and KIIs were conducted among chemists (n = 18) and dair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…Surprisingly, both para-veterinarians and veterinarians reported advising ABST only a few times, raising significant concerns ( Figure 9 ). Similar findings have been documented in other studies, highlighting the low prevalence of ABST in their respective areas ( 29 , 39 ). This raises concerns because empirical antibiotic prescriptions can lead to treatment failures, prolonged treatment durations, and ultimately reduced antibiotic efficacy in animals ( 40 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Surprisingly, both para-veterinarians and veterinarians reported advising ABST only a few times, raising significant concerns ( Figure 9 ). Similar findings have been documented in other studies, highlighting the low prevalence of ABST in their respective areas ( 29 , 39 ). This raises concerns because empirical antibiotic prescriptions can lead to treatment failures, prolonged treatment durations, and ultimately reduced antibiotic efficacy in animals ( 40 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our study findings found that para-veterinarians showed limited awareness of the consequences of antibiotic overuse and improper leading to AMR, whereas veterinarians demonstrated greater awareness ( Figures 4 , 5 ). These results indicate that all para-veterinarians are not aware of the factors responsible for AMR, aligning with studies in India showing limited knowledge among para-veterinarians about the consequences of inappropriate antibiotic prescriptions ( 28 , 29 ). Limited training programs for para-veterinarians contribute to this gap.…”
Section: Discussionsupporting
confidence: 82%
“…Recent studies in the region have underscored the limited availability and adoption of diagnostic tools and preventive measures by animal health service providers. This, in turn, has contributed to the imprudent use of antimicrobial agents in the study region [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Policies for controlling and optimizing the use of antimicrobials have been developed through legal provisions and program implementation, including surveillance of AMR and antimicrobial consumption in both human and animal sectors [34]. These are, however, seemingly not effective due to the laxity of the regulators to implement some of these AMR-related policies [43]. In a bid to control this, proper legislation must be framed to limit over-the-counter sales of antibiotics without a prescription from a veterinarian.…”
Section: Discussionmentioning
confidence: 99%